2019
DOI: 10.1186/s12935-019-0743-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Wnt ligands gene family and its relationship to prognosis in hepatocellular carcinoma

Abstract: Background The Wnt gene family members are known to participate regulating various normal and pathological processes including tumorigenesis. However, the association between Wnt ligands gene family and prognosis in hepatocellular carcinoma has not been systematically studied. Therefore, we evaluated the role of Wnt ligands gene family in hepatocellular carcinoma using publicly available data from The Cancer Genome Atlas (TCGA). Methods Clinical information and RNA-Seq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Six WNTs, including WNT5B, showed the opposite pattern of expression, suggesting that WNT5B may have anti-tumor activity in HCC. Meanwhile, there was no significant difference in WNT5A expression in tumor and adjacent normal tissue ( Dong et al, 2019 ).…”
Section: Role Of Wnt5b In Cancermentioning
confidence: 95%
“…Six WNTs, including WNT5B, showed the opposite pattern of expression, suggesting that WNT5B may have anti-tumor activity in HCC. Meanwhile, there was no significant difference in WNT5A expression in tumor and adjacent normal tissue ( Dong et al, 2019 ).…”
Section: Role Of Wnt5b In Cancermentioning
confidence: 95%
“…Wnt ligands have been investigated to activate the Wnt/β-catenin pathway through FZD7 in HCC cells and may play a role during hepatocarcinogenesis 27 . Both WNT3 and WNT3A are independent prognostic factors for hepatocellular carcinoma (HCC) 28,29 , and silencing WNT3A inhibits the growth of liver cancer 30 . In TME module 0, it is suggested that activated hepatocytes are malignant, and progression is promoted through specific active interactions.…”
Section: Resultsmentioning
confidence: 99%
“…WNT5B has been implicated in oncogenesis and developmental processes, including regulation of cell fate and patterning during embryogenesis. Ever report indicated WNT5B could serve as a prognostic biomarker in hepatocellular carcinoma [ 34 ]. RUNX2 , a transcription factor, acts as an essential factor in osteoblast differentiation and bone development and regulates a much wider tissue range [ 35 ], it could promote breast cancer bone metastasis by increasing integrinα5-mediated colonization [ 36 ].…”
Section: Discussionmentioning
confidence: 99%